Comparative Study of the Psychological Characteristics Athletes in terms of Individual Sports and the Team - Lidya Erika; Yahya Eko Nopiyanto; Defliyanto (Universitas Bengkulu, 2023)
This research was aimed to investigate: (1) the psychological characteristics of SMANKO Bengkulu Province athletes in terms of individual sports, (2) in terms of team sports, (3) the psychological characteristic differences of SMANKO Bengkulu Province athletes in terms of individual and team sports. This research employed the quantitative with comparative design. The subjects in this research were 56 athletes, namely 28 individual athletes and 28 team sports athletes. The data collection technique was conducted with the psychological skills inventory for sports that adopted from Mahoney, Gabriel & Perkins, (1987). Data were analyzed using t-test with a significant level of 0.05. The data were collected using the Psychological Skills Inventory for Sports questionnaire and analyzed using the independent sample t test. The research findings revealed that: (1) the psychological characteristics of SMANKO Bengkulu Province athletes in terms of individual sports, (2) the psychological characteristics of SMANKO Bengkulu Province athletes in terms of team sports are in high category, (3) there were no significant differences in the psychological characteristics of SMANKO Bengkulu Province athletes in terms of individual and team sports values = 0.508 > 0.05.